Characterization of the residual biochemical components of sequentially extracted banana peel biomasses and their environmental remediation applications. (15th April 2019) - Bediako, John Kwame; Sarkar, Amit Kumar; Lin, Shuo; Zhao, Yufeng; Song, Myung-Hee; Choi, Jong-Won; Cho, Chul-Woong; Yun, Yeoung-Sang
Graphical abstract: Highlights: Banana peel showed prospects for improved adsorption of cationic and anionic species. Sequential extraction enabled identification of key components for adsorption. Lipid-free biomass showed the maximum capacity for anionic adsorbate. Lipid- and protein-free biomass showed highest uptakes for cationic adsorbates. Abstract: After consumption of the inner fleshy fruit, the banana peel like many other fruit peels is usually disposed of unprocessed. For sustainable development, agro-wastes including banana peels need to be converted into valuable products that will be beneficial to human and the environment. In this study, biochemical components including lipids, proteins and structural polysaccharides were sequentially extracted from banana peel, and the residuals were characterized by FE-SEM/EDX, FTIR, XRD, TGA/DSC, XPS and elemental analysis. Owing to rapid industrialization, toxic species such as metals and dyes are consistently released into the aquatic environments. Therefore, the residual biomass samples were evaluated for environmental remediation application. The adsorption performances were outstanding, with uptakes reaching 1034, 279 and 152 mg/g, for methylene blue, lead and platinum, respectively. This study thus suggests that sequential extraction and detailed characterization are useful for identification of key contributing components for development of high-performance agro-waste-based adsorbents for water treatment.